Nitrogen limitation of chemostat-grown Rhizobium etli elicits higher infection-thread formation in Phaseolus vulgaris - Brelles Mariño, Graciela (1996)
The symbiotic association between rhizobia and legume roots is a complex process involving many steps. An infection thread is a tubular structure of host origin formed during the infection of legume roots by rhizobia. Previous studies with batch cultures have reported that optimal attachment of rhizobia to root hairs coincides with nutrient limitation. In this study, the ability of chemostat-grown, nutrient-limited Rhizobium etli cells to form infection threads with its symbiotic partner Phaseolus vulgaris was investigated. Rhizobia were grown in a chemostat in synthetic media under C- or N-limiting conditions. Infection-thread formation was examined after inoculation of seedlings with a rhizobial cell suspension from each treatment. The number of infection threads was estimated by light microscopy after staining root sections with o-toluidine. Exopolysaccharide (EPS) production was also measured, and the cellular content and electrophoretic pattern of lipopolysaccharide (LPS) determined semiquantitatively. N-limited cells showed a markedly higher infectivity (measured as infection-thread formation) than C-limited cells. With one of the two bean cultivars used, the number of infection threads produced by N-limited cells was higher than that produced by exponentially growing cells in batch cultures. The higher infectivity of N-limited cells was correlated with higher EPS production. Electrophoretic analysis of LPS showed that C- and N-limited cells shared a common profile but the relative concentration of short LPS forms differed.